Metode Guru Al-Qur’an Hadits Dalam Mengatasi Kesulitan Baca Tulis Al-Qur’an Pada Siswa Kelas V Di Mi Nurul Islahil Islami - samsul31 samsul31 (IQRO: Journal of Islamic Education, 2022)
The purpose of this study is to reveal the concept of the Qur'an Hadith, how the method of the Teacher of the Qur'an hadith in overcoming the difficulty of reading and writing the Qur'an at MI Nurul Islahil Islami. To reveal the obstacles and obstacles faced by teachers of the Qur'an hadith in overcoming the difficulty of reading and writing the Qur'an at MI Nurul Islahil Islami. This research uses qualitative research that uses a descriptive qualitative approach where in this study using three methods. Metdoe observations, interviews and documentation. The techniques in this study used data reduction, data display and data verification. The data in this study were checked for the validity of the data using the technique of prolonging the research time, persistence of observations, trianggulation. The results of this study show that the method of the Teacher of the Qur'an hadith in overcoming the difficulty of reading and writing the Qur'an in grade V students at MI Nurul Islahil Islami Kateng Village which contains the qira'ah method, the kitabi method.